Problems faced by the Cretan tourism industry as perceived by the business people - Andriotis, Konstantinos (My University, 2003)
Demand for vacations in Crete has increased rapidly. The subsequent expansion of tourism activities has resulted to many problems. However, there is a lack of studies investigating the opinions of tourism business people to these problems. As a result, the current study was undertaken using as a sample 146 owners/managers of tourism enterprises with the aim of examining the problems faced by the Cretan tourism industry and to provide recommendations for their solution. From the findings it is evident that the Cretan tourism enterprises face a variety of problems demanding immediate actions by the public and private sector for their solution.
Keywords: Crete; Dependence on tour operators; Problems; Seasonality; Solutions; Tourism industry